Utilisation of turboelectric distribution propulsion in commercial aviation: A review on NASA’s TeDP concept - Al Rashed, Mosab; Nikolaidis, Theoklis; Pilidis, Pericles; Jafari, Soheil (Elsevier, 2021)
Emissions produced by the aviation industry are currently a severe environmental threat; therefore, aviation agencies and governments have set emission targets and formulated plans to restrict emissions within the next decade. Hybrid aircraft technology is being considered to meet these targets. The importance of these technologies lies in their advancements in terms of aircraft life cycles and environmental benignity. Owing to these advancements, hybrid electric systems with more than one power source have become promising for the aviation industry, considering that the growth of air traffic is projected to double in the next decade. Hybrid technologies have given future hybrid fans and motor-fan engines potential as alternative power generators. Herein, Turboelectric Distributed Propulsion (TeDP) is discussed in terms of power distribution and power sources. The fundamentals of turbofan and turboshaft engines are presented along with their electricity-generation mechanism. TeDP is discussed from a design viewpoint, with a detailed discussion of different types of hybrid electric and turboelectric systems. Examples of proposed TeDP aircraft models and numerical modelling tools used to simulate the performance of TeDP models are reviewed. Finally, innovative turboelectric systems in which electric power savers and mechanical gear changers have been discarded for weight optimisation are presented along with other prospective models, engines, approaches, and architectures. The findings of this review indicate the knowledge gaps in the field of numerical modelling for NASA’s TeDP and its capability to increase the efficiency by up to 24% with a 50% reduction in emissions relative to those of conventional gas turbines.
Keywords: Futuristic propulsion systems; Numerical modelling and simulation; Turboelectric distributed propulsion; Hybrid aircraft engines; Turboelectric power